2021
DOI: 10.3389/fphar.2021.657826
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Isoimperatorin Against Influenza A Virus in vitro and its Inhibition of Neuraminidase

Abstract: Influenza A virus (IAV) poses a severe threat to human health and is a major public health problem worldwide. As global anti-influenza virus drug resistance has increased significantly, there is an urgent need to develop new antiviral drugs, especially drugs from natural products. Isoimperatorin, an active natural furanocoumarin, exhibits a broad range of pharmacologic activities including anticoagulant, analgesic, anti-inflammatory, antibacterial, anti-tumor, and other pharmacological effects, so it has attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Madin-Darby canine kidney (MDCK) cell was a gift from the Institute of Respiratory Diseases of Guangzhou Medical University and the State Key Laboratory of Respiratory Diseases (Guangzhou, China). MDCK cells were maintained in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% fetal bovine serum, 100 U/ml penicillin, and 100 U/ml streptomycin at 37 °C under 5% CO 2 ( Lai et al, 2021 ). The human lung microvascular endothelial cell (HULEC-5a) was obtained from The Global Bioresource Center (ATCC CRL-3244).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Madin-Darby canine kidney (MDCK) cell was a gift from the Institute of Respiratory Diseases of Guangzhou Medical University and the State Key Laboratory of Respiratory Diseases (Guangzhou, China). MDCK cells were maintained in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% fetal bovine serum, 100 U/ml penicillin, and 100 U/ml streptomycin at 37 °C under 5% CO 2 ( Lai et al, 2021 ). The human lung microvascular endothelial cell (HULEC-5a) was obtained from The Global Bioresource Center (ATCC CRL-3244).…”
Section: Methodsmentioning
confidence: 99%
“…The experimental method of plaque reduction was based on a previous description ( Furuta et al, 2002 ), as follows: MDCK cells (6 ×10 5 cells/well) were seeded in 12-well plates and cultured at 37 °C under 5% CO 2 for 24 h ( Lai et al, 2021 ). After infection with influenza virus, MOI 0.01, MDCK, and HULEC-5a cells were incubated for 48 h. The cells were then washed with phosphate buffer saline (PBS) and the supernatants collected from the virus-infected HULEC-5a and MDCK cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28][29][30][31]. Isoimperatorin (Figure 1) is a naturally occurring furanocoumarin present in this herb, and it has been reported that isoimperatorin exhibits potent antitumor [32][33][34], antibacterial [35,36], anti-inflammatory [37], analgesic [38], antioxidant [39][40][41] and antiviral [42,43] properties. Most studies involving the separation of isoimperatorin and related compounds from the roots of O. koreanum focus on the determination of relative quantities and biological efficacies, as well as the origin discrimination of the plant materials [44][45][46].…”
Section: Introductionmentioning
confidence: 99%